EFEKTIVITAS MODEL PEMBELAJARAN STAD DALAM MENINGKATKAN HASIL BELAJAR FISIKA - Manogari Sianturi (Jurnal Dinamika Pendidikan, 2016)
This research was conducted by the low result of physics study of 17 Agustus 1945 Senior students in Jakarta. The low result of physics study caused by the teaching methods which is still focused on teacher-centered. One of the improvemens in teaching and learning of Physics that can be done is to adopt a creative learning physics and applied so as to help students understand the concepts of physics. STAD learning model is one of the creative learning and aplikatif.This research aims is to determine the effectiveness of using learning model STAD to increasing the concept of energy and power. The subjects were students of class X is 42 people were divided into experimental class and control class. The data were collected from both groups and were analyzed using SPSS 22 for windows. The results of data analysis obtained that the mastery of the concepts of Physics students experimental group increased by an average of 31.14 from 44.38 into 75.52, higher than the control kolompok with an increase of an average of 14:13 of 45.00 into 59.13. These results revealed that Ho is rejected and Ha accepted.Therefore it can be concluded that the model of STAD can be effectively improved the result of physics study.Keywords : STAD, teacher-centered, result of Physics study